Powers of district land administrator in managing abandoned commercial land development projects : a case study of Kelantan - Mohd Helmi Mat Zin; Universiti Sultan Zainal Abidin . Faculty of Law and International Relations (2020)
Many development projects have been approved by the Kelantan State Authority to
bolster the economic growth of the state and to give a great impact on the value of
urban real estates. Unfortunately, most of the approved projects have not been
completed within the time period set by the State Authority. The District Land
Administrator (DLA) has been entrusted with the duties to ensure and monitor the
performance of the projects pursuant to the provisions of the National Land Code
1965 (NLC). Cursory literature review identified that the DLA is not able to supervise
the completion of the projects due to the lack of knowledge of his statutory powers.
Furtherrnore, the DLA has been reluctant to exercise his powers to commence legal
action against developers for non-performance due to the fear that the developers
might make counterclaim against the office of the DLA. Therefore, this research has
as one of its objectives to examine the powers and duties of the DLA in supervising
the performance of commercial land development projects. In the course, the research
will analyse the Kelantan state land administration framework, identify the main
factors that have reduced the eff ctiveness of the DLA against the proprietors or
developers of the abandoned proj cts, and suggest solutions to improve the functions
of the DLA. This research applied the qualitative method in data collection
comprising both primary and secondar sources. Primary sources comprised of
Federal legislations and State enactment . ca la minutes of Investment Committee
Meetings and interview with the officers from the Office of the Director for Land and
Economic Planning Unit (EPU). Secondary sources included books, news reports, and
scholarly articles from law journals, seminars and the Internet. The research showed
that the DLA has power under the NLC to monitor the performance of commercial
land development projects. However, research highlighted that the DLA is unable to
perform his duties due to the existence of several external factors that are beyond his
control including the challenges within the institution of land administration, such as
lack of expertise and knowledge among the officers, lack of clear policy guidelines
from the state or federal level, lack of political will, and limited fmancial resources
allocated for enforcement. The study concluded that the DLA plays a vital role in
determining the performance of land development activities within his own district. In
order to perform efficiently, the DLA need to be a qualified and competent person to
lead land administration. Besides that, aspects relating to improving enquiry
procedures, providing clear enforcement guidelines, establishing special t am
monitor the abandoned projects and extending the powers of the DLA should be
similar to that of the Registrar of Titles. Therefore, reforms to the land administration
institutions are necessary to ensure the DLA's statutory powers can be exercised
effectively within the ambit of the enabling statute.
1. Introduction -- 2. Powers and duties of district land administrator in land development process -- 3. The structure of Kelantan land administration -- 4. Abandoned commercial land development project in Kelantan -- 5. Recommendations and conclusion
Thesis (Degree of Master of Law) - Universiti Sultan Zainal Abidin, 2020
Includes bibliographical references (leaves 146-149)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Law and International Relations -- Dissertations; Dissertations, Academic; Land tenure -- Law and legislation -- Malaysia; Land use -- Law and legislation -- Malaysia